Fixed gonadotropin-releasing hormone antagonist protocol versus gonadotropin-releasing hormone agonist long protocol in patients with polycystic ovary syndrome treated for intracytoplasmic sperm injection cycles - Khalifa, Emad Eldin Abd Elrahman; Orief, Yasser Ibrahim; Said, Tamer Hanafy Mahmoud; Elmaksoud, Doaa Abd Allah Abd (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Women with polycystic ovary syndrome (PCOS) are at risk of developing ovarian hyperstimulation syndrome (OHSS) during ovarian stimulation. Use of GnRH antagonist in the general sub fertile population is associated with lower incidence of (OHSS) than agonists and similar probability of live birth but it is unclear. Our Objective was to compare the fixed GnRH antagonist and GnRH agonist long protocols in patients with PCOS undergoing IVF. Methods: In this randomized controlled trial (RCT), 200 patients with PCOS were randomly allocated in two groups: long GnRH (n = 100) and fixed GnRH antagonist protocol (n = 100). Results: There is significant difference was observed in chemical pregnancy rate (46.0% versus 31.0%), and clinical pregnancy rate (43.0% versus 29.0%) in agonist and antagonist protocols, respectively. Duration of stimulation was significantly higher in agonist group (13.58 versus 12.381 days), respectively. Total number of ampoules of gonadotrophin is comparable in both groups (t=1.914, p=0.057). Conclusions: The use of GnRH antagonists is more advantageous than GnRH agonists in relation to shorter duration of stimulation thus allowing a reduction in the treatment time that makes COS less costly and better patient compliance. In this study GnRH agonist shows higher pregnancy rate than antagonist, so larger studies needed to clarify their roles.